The Urgency of Education Regarding Testing the Mediation of Dividend Policy on the Effect of Expropriation, Big Double Shareholders, and Company Value - Yovita Vivianty Indriadewi Atmadjaja; I Made Narsa; Andry Irwanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to explain the importance of education to examine and analyze dividend policy as a variable on the effect of expropriation, several large shareholders, and firm value. The type of research used is quantitative explanatory using secondary data, namely 2015 to 2020 annual reports taken from the official website of the Indonesia Stock Exchange (IDX), Indonesian Capital Market Exchange (ICMD), and the website www.investing.com. The sampling method in this study was purposive sampling so that a sample of 3,328 data was obtained. The data analysis method used in this study uses the unbalanced data panel and path analysis method with the Eviews software program. The study's results prove that dividend policy does not mediate between expropriation and firm value but instead becomes a variable that mediates several large shareholders with firm value. This means related party transactions as proxies cannot be used as a benchmark in assessing a company.